Saung Cave characteristics at Pengembur Village, Pujut District, Central Lombok, as a bats (Chiroptera) Habitat - Akram, Muhammad Zaki Ali; Syaputra, Maiser; Wahyuningsih, Endah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The Saung Cave is located in Pengembur Village, Pujut District, Central Lombok, and serves as a natural habitat for bats. This study aims to determine the characteristics of Saung Cave as a habitat for bats (Chiroptera), which includes the cave's dimensions, environmental conditions, surrounding vegetation, guano thickness, and other wildlife present in the cave. The methods used in this research involve observation, measurement, and field recording to assess the characteristics of Saung Cave as a bat habitat. The results indicate that the cave dimensions are 11.2 m wide, 13.2 m high, and 64.13 m deep. Saung Cave has a daily temperature ranging from 25.5ºC, humidity of 59.7%, and light intensity of 95 lx. The surrounding vegetation includes large-leaved mahogany (Swietenia macrophylla), small-leaved mahogany (Swietenia mahagoni), and gamal (Gliricidia sepium). Other wildlife found in the cave includes house centipedes (Scutigera coleoptrata), barn owls (Tyto alba), Nusa Tenggara rat snakes (Coelognathus subradiatus), curved-toed geckos (Cyrtodactylus marmoratus), and brown recluse spiders (Loxosceles reclusa). The thickness of guano in Saung Cave is 19 cm.